Low achievers and vocabulary learning strategies / Surina Nayan and Hariharan N Krishnasamy - Nayan, Surina; Krishnasamy, Hariharan N (Universiti Teknologi MARA, Perlis, 2019)
This is a conceptual paper on low achievers and vocabulary learning strategies. The paper focuses on what vocabulary is, its importance, types of vocabulary learning strategies, low achievers and their vocabulary learning, the importance of explicit teaching of vocabulary learning strategies to low achievers and also studies done on them. Low achievers need to be made aware of the existence of these strategies and employ them in their learning. This is because they have less motivation to learn English as they are weak in this subject. Learners should also be taught on these strategies explicitly so that they are able to be autonomous in their learning. The knowledge on the strategies that they get will be helpful later in the work place as they will encounter various types of vocabulary that are related to their job. The paper ends with the conclusion and recommendations on ways to help low achievers to enhance their vocabulary knowledge.